2016
DOI: 10.1021/acsbiomaterials.6b00705
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Generated Poly(allyl alcohol) Antifouling Coatings for Cellular Attachment

Abstract: Conformal poly(allyl alcohol) (PAA) coatings were grown on a biomedical grade polyurethane scaffold using pulsed plasma polymerization of the allyl alcohol monomer. The creation of a continuous wave polymer primer layer increases the interfacial adhesion and stability of a subsequent pulsed plasma deposited PAA film. The resulting PAA coatings are strongly hydrophilic and remain unchanged following seven days incubation in biological media. Films prepared through this two-step process promote human dermal fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Similarly, their 2D HSQC spectra revealed that the protons with resonance in the range of 3.30-3.45 ppm corresponded to two different carbons with chemical shifts 68.2 and 72.0 ppm. The latter 13 C shift, labeled as d, resembles the peak signal for the A6CC monomer, confirming that the 2D HSQC cross-peak 1 H 3.32 ppm- 13 C 72.0 ppm is linked to the methoxy group from the former allyl group. For the polymerized A6CCs, the peak was denoted as d' [34].…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Similarly, their 2D HSQC spectra revealed that the protons with resonance in the range of 3.30-3.45 ppm corresponded to two different carbons with chemical shifts 68.2 and 72.0 ppm. The latter 13 C shift, labeled as d, resembles the peak signal for the A6CC monomer, confirming that the 2D HSQC cross-peak 1 H 3.32 ppm- 13 C 72.0 ppm is linked to the methoxy group from the former allyl group. For the polymerized A6CCs, the peak was denoted as d' [34].…”
Section: Resultssupporting
confidence: 52%
“…As shown in Figure 5a, the closed ring structure of the monomer implies two cross-peaks between diastereotopic protons forming the cyclic carbonate, labeled as c ( 1 H 4. 13 5b) and A6CC-90 (Figure S5). Similarly, their 2D HSQC spectra revealed that the protons with resonance in the range of 3.30-3.45 ppm corresponded to two different carbons with chemical shifts 68.2 and 72.0 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of studies have been focused on the synthesis and characterization of plasma polymers for biomedical applications, only a few have investigated their stability in aqueous media and studied eventual bacteria attachment and biofilm formation. [8][9][10][20][21][22] A biodegradable polymer coating synthesized by plasma at atmospheric pressure using a dielectric barrier discharge (DBD) which operates in 4 nitrogen or argon -ethyl lactate mixture have been proposed as drug delivery system by Laurent et al 19 . Moreover, the ethyl lactate degradable plasma polymer seemed to enable the growth of primary human endothelial cells, therefore showing its potential for vascular applications.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of bacteria adhesion and biofilm formation of mixed cultures of Salmonella typhimuriumm, Staphylococcus epidermidis and Pseudomonas fluorescens could be achieved on 12-crown-4-and triglyme-plasma-coated stainless steel surfaces. 22 Recently, Watkins et al 21 reported on the capacity of pulsed plasma formed poly(allyl alcohol) films to impede bacteria adhesion and at the same time allow attachment and proliferation of dermal fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%